Technical and economic aspects of dc-ac minigrid construction - E. A.-Z. Dzhendubaev (Вестник Северо-Кавказского федерального университета, 2023)
The article deals with issues related to the advantages of AC power industry in comparison with the existing AC power industry. As an example, a DC-AC minigrid is considered, which includes: a gas turbine engine, the rotor of which rotates at a frequency of 12000 rpm; high-speed four-pole asynchronous generator with capacitor self-excitation and EMF frequency of about 400 Hz in idle mode; step-up transformer (400 Hz), to the secondary winding of which a rectifier with a filter is connected; DC power lines; a step-down semiconductor DC transformer to which a DC load is connected. Known expressions are given, as well as the results of calculations, which confirm the possibility of a significant improvement in weight, size and technical and economic indicators of DCAC minigrids compared to AC minigrids. Estimated calculations show that the effectiveness of the proposed technical solution depends on the proportion of “hidden” DC consumers and the remoteness of the generator from the load.